Perancangan sistem absensi siswa dengan menerapkan SSO (Single sign on) di SMKN 1 Lembah Melintang - Ardiyah, Ismi; Riri Okra; Hari Antoni Musril; Khairuddin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The author conducted research at SMK Negeri 1 Lembah Melintang that in the implementation of the student attendance process at SMKN 1 Lembah Melintang it was deemed not optimal, this was because the system used was still manual. With the existing problems, several problems arise, especially in the student attendance process. Therefore, a system is needed that will make it easier for teachers to attend students at SMKN 1 Lembah Melintang. The making of this student attendance system uses the PHP/MySql programming language with the research method used, namely Research and Development (R&D). The model used is the ADDIE version (analyze, design, develop, implement, and evaluate) by applying the waterfall. And to test the product, the author uses the validity test, practicality test and effectiveness test. Based on the research that has been done, a student attendance system is produced by implementing SSO (single sign on) at SMKN 1 Lembah Melintang. The results of the validity tests that have been carried out by 3 validators, namely computer science experts regarding this product, obtained a value of 0.75, which is valid. The results of the practicality test conducted by 2 teachers of SMK Negeri 1 Lembah Melintang with a value of 1.03 which is very practical. And the results of the effectiveness test with 10 teachers obtained a value of 0.85 which is very effective.